The Identification Reason Floods in the District South Palangga, South Konawe, Southeast Sulawesi, Indonesia - Rizda Sandiva; Aulia Mutmainna; Ardinawati (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Flooding is one of the most frequent natural disasters in Indonesia, particularly in Southeast Sulawesi. The consequences of floods include damage to infrastructure, public health issues, and loss of life. Understanding the underlying causes of flooding is essential for developing effective mitigation strategies. This study focuses on identifying the contributing factors to flooding in South Palangga District, South Konawe Regency. Objective: The objective of this study is to analyze the factors that contribute to flood occurrences and their impacts on the local community in South Palangga District. Methods: This study employs a qualitative research design utilizing online data collection methods. Secondary data sources include official government statistics and meteorological data from the Meteorology, Climatology, and Geophysics Agency (BMKG). Data analysis was conducted through data presentation and conclusion drawing techniques. Results: The findings indicate that high rainfall is the primary factor contributing to flooding in the region, with a noted increase in flood events between 2018 and 2020. A significant flood event on March 31, 2024, caused considerable physical damage and disrupted local economic activities. Conclusion: This study concludes that excessive rainfall is the main driver of flooding in South Palangga District, South Konawe Regency. The increasing trend in flood events highlights the urgent need for comprehensive mitigation strategies and integrated spatial planning to reduce future flood risks and protect the affected communities. Keywords: Flood, Rainfall, Impact, South Palangga District, Mitigation